Spectral Characteristics and Photosensitization of TiO2 Nanoparticles in Reverse Micelles by Perylenes - Hernández, Laura (2012)
We report on the photosensitization of titanium dioxide nanoparticles (TiO2 NPs) synthesized inside AOT (bis(2-ethylhexyl) sulfosuccinate sodium salt) reverse micelles following photoexcitation of perylene derivatives with dicarboxylate anchoring groups. The dyes, 1,7-dibromoperylene-3,4,9,10-tetracarboxy dianhydride (1), 1,7-dipyrrolidinylperylene-3,4,9,10-tetracarboxy dianhydride (2), and 1,7-bis(4-tert-butylphenyloxy)perylene-3,4,9,10-tetracarboxy dianhydride (3), have considerably different driving forces for photoinduced electron injection into the TiO2 conduction band, as estimated by electrochemical measurements and quantum mechanical calculations. Fluorescence anisotropy measurements indicate that dyes 1 and 2 are preferentially solubilized in the micellar structure, creating a relatively large local concentration that favors the attachment of the dye to the TiO2 surface. The binding process was followed by monitoring the hypsochromic shift of the dye absorption spectra over time for 1 and 2. Photoinduced electron transfer from the singlet excited state of 1 and 2 to the TiO2 conduction band (CB) is indicated by emission quenching of the TiO2-bound form of the dyes and confirmed by transient absorption measurements of the radical cation of the dyes and free carriers (injected electrons) in the TiO2 semiconductor. Steady state and transient spectroscopy indicate that dye 3 does not bind to the TiO2 NPs and does not photosensitize the semiconductor. This observation was rationalized as a consequence of the bulky t-butylphenyloxy groups which create a strong steric impediment for deep access of the dye within the micelle structure to reach the semiconductor oxide surface.